ANALISA NILAI CBR SOAKED DAN UNSOAKED UNTUK LAPISAN SUBGRADE PADA TANAH MERAH NGELING JEPARA - Khotibul Umam (Universitas Tidar, 2021)
Problems associated with the subgrade (subgrade) of the structure on the pavement include deformation which is caused by traffic loads, soil shrinkage due to changes in moisture content and uneven soil bearing capacity. In any civil engineering work, it is generally established on the ground. With the development of the times, more and more agricultural lands are used in the construction of road access. In general, red soil is easy to absorb water, contains moderate organic matter, and has a neutral acidity. In the area of Ngeling Village, Jepara, land is generally used for farming and now much of it has been converted into land for building roads. In the implementation of road construction, the price of CBR for land is very important and influential. The subsoil layer in the road structure may consist of original soil, excavated soil and compacted soil which can reach a density of at least 100%. In this study, it was found out how much the laboratory CBR value of both CBR Soaked and CBR Unsoaked from the original land in Ngeling Village, Jepara. In addition, it can also be seen that the CBR value in the worst soil conditions is obtained from CBR Soaked (immersion). The CBR value of the soil with saturated water immersion obtained a value of 3.8553%, which is categorized as bad for sugbgrade, while the land without being soaked has a value of 10.925% which is categorized as good for subgrade.